2014
DOI: 10.1002/adem.201400127
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐W Dispersed Gamma Radiation Shielding Materials

Abstract: We present a nano‐W dispersed polymer composite whose gamma attenuation is greatly enhanced. In situ pulverization and simultaneous encapsulation of polyethylene (PE) onto the nano‐W particles was successfully performed by ball milling. Adhesive encapsulation of PE was observed by means of interstitial diffusion of atomic W at the boundary using transmission electron microscope. Prepared nano‐W/PE particles were dispersed into ethylene‐propylene‐based polymer mixture using melt mixing. Attenuation of gammas fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Nevertheless, other elements of the equipment involved in the Moon and Mars human exploration missions could also be of critical importance, with the radiation shielding materials, sensors for monitoring astronaut and vehicle status and health, advanced materials for water and air purification and waste neutralization being among the most important. Recent progress has been achieved in the design and testing of advanced nanostructured radiation shielding materials based on composites, polymers, and nanoparticles that serve as a radiation‐absorbing agent . Metamaterials‐based, flexible, self‐healing highly sensitive sensors of various types have also been developed on the basis of the dynamic, advanced materials .…”
Section: Remote Horizons: Materials Challenges For Moon and Mars Explomentioning
confidence: 99%
“…Nevertheless, other elements of the equipment involved in the Moon and Mars human exploration missions could also be of critical importance, with the radiation shielding materials, sensors for monitoring astronaut and vehicle status and health, advanced materials for water and air purification and waste neutralization being among the most important. Recent progress has been achieved in the design and testing of advanced nanostructured radiation shielding materials based on composites, polymers, and nanoparticles that serve as a radiation‐absorbing agent . Metamaterials‐based, flexible, self‐healing highly sensitive sensors of various types have also been developed on the basis of the dynamic, advanced materials .…”
Section: Remote Horizons: Materials Challenges For Moon and Mars Explomentioning
confidence: 99%
“…Whereas, magnesium alloys superplasticity requires some hard conditions, i.e., the superplasticity of commercial magnesium alloys could be reached only at a reasonable stable and fine grain structure (usually less than 10 mm) [2,12e15]. In order to reduce the grain size, complicated materials processing methods such as, friction stir processing [2,16,17], submerged friction stir processing [18,19], powder metallurgy [14], high-ratio differential speed rolling [20], equal channel angular extrusion [21] and high pressure torsion [22], have been used. However, grain refinement not only complicates the material preparation but also requires low temperature SPF to avoid grain growth during forming.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer‐based composites, such as polyethylene, rubber, and epoxy composites, have been intensively studied. Polyethylene based composites containing tungsten , boron carbide and boron nitride fillers were fabricated. Kalosh prepared ultra‐high molecular weight polyethylene based composites which contained 60 wt% tungsten and the results showed that the linear attenuation coefficient for 122 keV was 3.43 cm −1 .…”
Section: Introductionmentioning
confidence: 99%